ADVERTISING DISCOURSE AS A TOOL OF PERSUASION: FUNCTIONAL, STYLISTIC AND COMMUNICATIVE ASPECTS - Шпирка, Анастасія (SWorldJournal, 2025)
This article explores advertising discourse as a specific form of mass communication that integrates informational, emotional, and persuasive functions. The authors analyze the stylistic features of advertising language and its capacity to influence consu